2015
DOI: 10.1016/j.micres.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Illumina MiSeq investigations on the changes of microbial community in the Fusarium oxysporum f.sp. cubense infected soil during and after reductive soil disinfestation

Abstract: Although reductive soil disinfestation (RSD) is increasingly used for the control of soil-borne diseases, its impact on the soil microbial community during and after RSD remains poorly understood. MiSeq pyrosequencing, real-time PCR and denaturing gradient gel electrophoresis were performed to investigate the changes of microbial community in the Fusarium oxysporum f. sp. cubense (FOC) infected soil during RSD and at the simulative banana cultivation after RSD. The results showed that RSD significantly increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(80 citation statements)
references
References 51 publications
2
77
0
1
Order By: Relevance
“…The Biolog system has been used for environmental research by many researchers [20,43], allowing for the monitoring of changes in the population of microorganisms in the soil and other ecosystems under the influence of various factors. The assessment of the impact of fertilizer (organic or mineral) addition on the population of microorganisms is important due to the functions they perform in the soil [44]. The results of our study show, that all of the tested wastes affected the functional diversity of soil microbial communities, including bacteria, fungi and anaerobes in a characteristic way.…”
Section: Discussionmentioning
confidence: 63%
“…The Biolog system has been used for environmental research by many researchers [20,43], allowing for the monitoring of changes in the population of microorganisms in the soil and other ecosystems under the influence of various factors. The assessment of the impact of fertilizer (organic or mineral) addition on the population of microorganisms is important due to the functions they perform in the soil [44]. The results of our study show, that all of the tested wastes affected the functional diversity of soil microbial communities, including bacteria, fungi and anaerobes in a characteristic way.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies (Bhat and Bhat, 1997;Biddle et al, 2013;Del Rio et al, 2010;Eichorst et al, 2013;Kumar et al, 2015) have indicated that they also can break down less-degradable organic carbon. Therefore, these TOC decomposers and organic acid producers could collaborate to control FOC (Huang et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…Clostridia are gram-positive anaerobic bacteria. Several studies have reported that the abundance of Clostridia species increases and it becomes the dominant bacteria after ASD treatment using plant material or low-concentration ethanol as a substrate [13,14,27]. During ASD, decreased oxygen utilization promotes the increased prevalence of anaerobic microbes [6,12,27].…”
Section: Discussionmentioning
confidence: 99%